Risk of anorexia and bulimia nervosa and its associated factors in undergraduate students - Díaz Muñoz, Gustavo Alfonso (Revista de Nutrição, 2022)
Objective To quantify the prevalence and related factors to the risk of anorexia and bulimia nervosa in undergraduate students at a private university in Bogotá, Colombia. Methods A cross-sectional study, which evaluated the frequency of food consumption, physical activity (International Physical Activity Questionnaire, short form), the risk of anorexia and bulimia nervosa (Sick, Control, One, Fat, and Food questionnaire) and demographic variables. The statistical analysis used a multivariate logistic regression model, where the outcome was the yes/no risk of anorexia or bulimia nervosa. Results A total of 1,545 university students participated. The average age was 19.2 years (+/-2.5), 65.7% were women, and 63.9% came from Bogotá. The risk of anorexia and bulimia nervosa was 27.6%. In the logistic regression, the risk was associated with female sex (OR 1.6 CI95% 1.2 to 2.1), daily consumption of cereals (OR 0.7 CI95% 0.6 to 0.9), daily fat consumption (OR 1.5 CI95% 1.1 to 2.1), eat light products (OR 1.8 CI95% 1.1 to 2.9), consume protein supplements (OR 0.4 CI95% 0.2 to 0.8), being in disagreement with physical activity for fun (OR 1.8 CI95% 1.1 to 3.1), and physical activity by appearance (OR 2.2 CI95% 1.6 to 2.9). Conclusions The prevalence of risk to anorexia and bulimia nervosa in the study sample is high. The associated factors were the consumption of cereals, fat, light products, and protein supplements. Physical activity by appearance and disagreement to do exercise by fun were associated with the risk of anorexia and bulimia nervosa. So it is recommended that universities implement awareness and education interventions to address this problem.